Pseudostatic analysis for seismic responses of extended piles considering inertial and kinematic effects. (1st February 2022) - Chiou, Jiunn-Shyang; Fu, Yu-Wei; Lee, Yi-Wun
Highlights: The pseudostatic approach considers piles under inertial and kinematic loadings. A weighted motion is used to combine ground motions at different depths. The system damping ratio combines viscous, radiation and hysteretic damping ratios. Inertial/kinematic participation factors depend on normalized excitation frequency. Near-fault motions impose pronounced kinematic loading on piles at deep depths. Abstract: This study proposes a pseudostatic approach for analyzing the seismic response of an extended pile under inertial and kinematic loadings. A structure–pile–soil pushover model is established. In the model, the inertial loading is simulated as a static force that is applied at the pile head, and the kinematic loading is simulated by imposing a ground displacement profile on the pile–soil interaction springs. This approach, based on a dynamic structure–pile–soil interaction model, comprises three aspects: inertial loading, kinematic loading, and combination of inertial and kinematic loadings. For the inertial loading, the capacity spectrum method is applied to obtain the maximum acceleration of the superstructure mass, using a weighted motion that combines contributions of excitations at various soil depths and an equivalent system damping ratio in terms of linear viscous damping, radiation damping, and hysteretic damping. For the kinematic loading, the ground displacement profile corresponding to the maximum ground surface displacement is analyzed through ground response analysis. For the combined action of inertial and kinematic loadings, because their maximum effects may not occur simultaneously, we construct the relationships of participation factors with the ratio of the excitation frequency to the system frequency. Examples are used to demonstrate the applicability of the proposed method.